(3GdGKfG YTQjI aj GdUhes - (3GdYGedj, HgGA GdOjf, HgGA GdOjf GdYGedj, eMeO Hf MSjf Hf YHO GdUeO, J (B1031(3g` (B1622(3es ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd GdUhe LfI ef GdfGQ (B... (3aCbhd Ef GdCehQ GdJj dG HO ddUGFe ef GLJfGHgG fhYGf GdChd CehQ jaSO GdUhe HGQJcGHgG hjJhba MUhd MbjbJg Ydi GLJfGHgG cGdCcd hGdLeGYs
(3BNQgG (B:s
(3BNQgG(B: (3GdMGOjI YTQ Ef JMSjf GdNdb ajg LhGR Ydi GdUQGW jhe jRd ajg GdCbOGe, GdKGfjI YTQ(B: (3Ef KhGH JdGhI BjI hGMOI ajg cKhGH NJe GdbQBf aj ZjQg(B. (3NJeJ GdGKfi YTQjI GdUhejIs
(3JGQjN GdJCdja(B: 1019(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 102s
(3GdPQjYI, L (B1: 82s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis